EFFECT OF MANUAL CONCRETE CASTING METHODS ON THE PERFORMANCE OF RIGID PAVEMENT - Yudi Sekaryadi (Jurnal HPJI (Himpunan Pengembangan Jalan Indonesia), 2026)
Abstract This study aims to analyze the effect of manual concrete casting methods on the performance of rigid pavement. The research methodology includes a review of the SNI Pd T-14-2003 standard and the 2013 General Specifications for Road and Bridge Works, field observations of construction activities, and the execution of slump tests, compressive strength tests, and thickness measurements. Manual concrete mixing was observed in this study due to the project's remote location and the lack of access to a batching plant. Slump testing on 30 specimens showed that 25 specimens yielded values ​​within the 20 mm to 60 mm range, while 5 specimens exceeded the maximum limit but remained within tolerance limits. Compressive strength testing on 20 specimens resulted in an average strength of 350.40 kg/cm², with a standard deviation of 1.39, a coefficient of variation of 0.4%, and a characteristic compressive strength of 350.06 kg/cm². The average pavement thickness across 20 test points was 270.88 mm; only 3 test points yielded values ​​below the design thickness, yet these remained within tolerance limits. Thus, it can be concluded that manual mixing and casting methods do not result in significant differences compared to methods utilizing batching plant equipment. Keywords: manual concrete casting; rigid pavement; slump test; compressive strength; pavement thickness Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh metode pengecoran beton secara manual terhadap kinerja perkerasan kaku. Metodologi penelitian mencakup tinjauan terhadap standar SNI Pd T-14-2003 dan Spesifikasi Umum Pekerjaan Jalan dan Jembatan Tahun 2013, observasi lapangan terhadap kegiatan konstruksi, serta pelaksanaan uji slump, uji kuat tekan, dan pengukuran ketebalan. Pencampuran beton secara manual diamati dalam penelitian ini karena lokasi proyek yang terpencil dan kurangnya akses ke batching plant. Dari pengujian slumo terhadap 30 benda uji, 25 benda uji memberikan nilai slump pada rentang 20 mm hingga 60 mm, sedangkan 5 benda uji memberikan nilai slump melampaui batas maksimum namun tetap berada dalam batas toleransi. Pengujian kuat tekan pada 20 benda uji menghasilkan kekuatan rata-rata sebesar 350,40 kg/cm², dengan deviasi standar 1,39, koefisien variasi 0,4%, dan kuat tekan karakteristik sebesar 350,06 kg/cm². Ketebalan perkerasan rata-rata dari 20 titik uji adalah 270,88 mm, dan hanya 3 titik uji yang memberikan nilai di bawah ketebalan desain, namun nilainya tetap berada dalam batas toleransi. Dengan demikian, dapat disimpulkan bahwa metode pencampuran dan pengecoran secara manual tidak menghasilkan perbedaan yang signifikan dibandingkan dengan metode yang menggunakan peralatan batching plant. Kata-kata kunci: pengecoran beton manual; perkerasan kaku; uji slump; kuat tekan; ketebalan perkerasan